Penggabungan Metode Fuzzy Simple Additive Weighting dengan Rank Order Centroid sebagai Pendukung Keputusan Penilaian Kemiskinan di Jawa Timur - Wike, Wike Nur; Jauhari, Mohammad Nafie; Nasichuddin, Achmad (Jurnal Riset Mahasiswa Matematika, 2023)
The purpose of this study is to determine the results of the combination of Fuzzy Simple Additive Weighting with Centroid Rank Order as a support for poverty assessment decisions in East Java Province.  Using a combination of Fuzzy Simple Additive Weighting and Rank Order Centroid is expected to provide better results. Decision support systems can help the government to determine the poverty status of a district or city in poverty reduction. Poverty itself is an important problem in life in many provinces. The problem of poverty triggers social problems that are closely related to the quality of education, crime, hunger, and others, which cause indirect disruption of stability and sustainability. Therefore, a decision support system is needed to make it easier for the government to determine the poorest districts or cities so that the government can aid programs or make strategies to reduce poverty. Fuzzy logic is a method that can be used to overcome uncertainty in decision making. One method in fuzzy logic to overcome uncertainty is to use the Fuzzy Simple Additive Weighting method. In the Fuzzy Simple Additive Weighting method, there is a selection of criteria that will later be weighted based on importance or priority using the Rank Order Centroid method. The criteria used in this study are life expectancy (AHH), literacy rate (AMH), per capita expenditure, and population. The membership function used is the Tringular Fuzzy Number representation. In this study, twenty four rules were given which were obtained from giving different weights to each criterion. So that twenty four of the poorest districts or cities were obtained. Then the final result is the name of the most Regency or City from the twenty four results, namely alternatives twenty seven and twenty eight, namely Sampang Regency and Pamekasan Regency which were entitled to assistance programs from the government.